An in vitro comparison of apically extruded debris using three rotary nickel-titanium instruments - Tamer Tasdemir; Kürsat Er; Davut Çelik; Hikmet Aydemir (Elsevier, 2010)
The aim of this in vitro study was to compare the amount of extruded debris using three rotary nickel-titanium (NiTi) instruments (ProTaper Universal, Mtwo, and BioRaCe). Materials and methods: Sixty freshly extracted human single-rooted mandibular premolars were randomly assigned into three groups of 20 teeth each. The root canals were instrumented using ProTaper Universal (Dentsply Maillefer, Ballaigues, Switzerland), Mtwo (VDW, Munich, Germany), or BioRaCe (FKG Dentaire, La-Chaux-de-Fonds, Switzerland) NiTi instruments. Debris and liquid extruded from the apical foramen during instrumentation were collected into tubes. Then, the liquid inside the tubes was removed by lyophilization, and the mean weight of the remaining debris was calculated for each group and compared. Data were then statistically analyzed using one-way ANOVA and post-hoc Tukey's tests. Results: There were significant differences in the amount of debris extruded among all groups (P < 0.01). The greatest amount of apical debris was extruded by the ProTaper Universal group and the least by the BioRaCe group. Conclusion: According to this study, all instrumentation techniques apically extruded debris through the apical foramen. However, the BioRaCe instruments induced less extruded debris than the ProTaper Universal and Mtwo rotary systems.